PENERAPAN METODE GBL UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF MATERI PECAHAN KELAS 4 SDN KELEYAN 1 BANGKALAN - Dimas Agung Saputro; Muhammad Syahrul Alim; Ika Dian Rahmawati (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
This study was conducted to determine the effectiveness of the Game-Based Learning (GBL) method in improving the cognitive learning outcomes of fourth-grade elementary school students on fraction material. The research employed a quantitative approach using a one-group pretest-posttest design involving 20 students as the research sample. Data were collected through pretest and posttest assessments and analyzed using the N-Gain test, Shapiro–Wilk normality test, and Paired Sample t-test. The results indicated an improvement in students' cognitive abilities after participating in game-based learning, as evidenced by the increase in the average score from 63.5 on the pretest to 84.9 on the posttest. The N-Gain analysis produced an average score of 0.61, which falls into the moderate category, with 25% of students achieving a high level of improvement and 75% achieving a moderate level. The normality test showed that the data were normally distributed, with significance values of 0.551 for the pretest and 0.498 for the posttest, both exceeding the 0.05 threshold. Furthermore, the Paired Sample t-test yielded a t-value of 57.410, which was greater than the t-table value of 2.093, with a significance value of 0.000, indicating a statistically significant effect of the implementation of the Game-Based Learning method on students' learning outcomes. Therefore, the Game-Based Learning method can serve as an effective instructional alternative, as it enhances students' understanding through more interactive, engaging, and enjoyable learning activities.